Effective Prevention and Treatment of Substance Use Disorders for Racial and Ethnic Minorities 2020
DOI: 10.5772/intechopen.91055
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Approaches to Developing an Effective Drug Treatment System

Abstract: Improving the effectiveness of the substance use disorder (SUD) treatment requires leadership approaches that have an impact on the effectiveness of drug treatment. To promote this positive system change, we define leadership beyond leaders' characteristics. We consider leadership as a developmental competency among individuals, as well as the relational role of followers and the enabling context of organizational climate which together create a system of influence. Using this developing framework, we discuss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Guerrero and Khachikian (2020) found that leaders could control financial plans and approaches to increase their care for vulnerable customers by relying on their transformational and executive competencies.…”
Section: Theoretical Framework and Backgroundmentioning
confidence: 99%
See 4 more Smart Citations
“…Guerrero and Khachikian (2020) found that leaders could control financial plans and approaches to increase their care for vulnerable customers by relying on their transformational and executive competencies.…”
Section: Theoretical Framework and Backgroundmentioning
confidence: 99%
“…The results showed that the audit team's cohesion is affected by the organisation's systems. Guerrero and Khachikian (2020) found that leaders could control financial plans and approaches to increase their care for vulnerable customers by relying on their transformational and executive competencies. Worthy et al, (2020) showed that leadership behaviours affect job satisfaction, indicating the need for focused training and leadership behaviour development.…”
Section: Theoretical Framework and Backgroundmentioning
confidence: 99%
See 3 more Smart Citations